Extracción de flavonoides a partir de los residuos del tomate de árbol (2022)
The objective of this work is to analyze and compare two different methods for the extraction of flavonoids from tree tomato epicarp residues, in order to select the extraction method that presents optimal conditions of operation and costs, and to carry out the respective conceptual design. To develop the general objective, it was necessary to compile bibliographic information on flavonoids, total polyphenols, chemical structure of tree tomato and its uses in the industry. It was also necessary to collect data on physicochemical characteristics, varieties, moisture content present in the fruit, to find a relevant relationship to the epicarp of the fruit, allowing to establish the variables manipulated in the pretreatments before and after the extraction process.